Recharge estimation of a small karstic aquifer in a semiarid Mediterranean region (southeastern Spain) using a hydrological model. Issue 2 (21st February 2012) - Touhami, I.; Andreu, J. M.; Chirino, E.; Sánchez, J. R.; Moutahir, H.; Pulido‐Bosch, A.; Martínez‐Santos, P.; Bellot, J.
Abstract Mediterranean aquifers are frequently subject to the joint effect of intensive exploitation and low recharge values. Besides, groundwater is the only available water resource in many Mediterranean regions. Groundwater recharge studies are therefore necessary to underpin water management practices. This manuscript presents a methodology to estimate groundwater recharge in a small limestone aquifer of southeastern Spain. The HYDROBAL model is used to calculate daily soil water balances on the basis of hydrological and soil data as well as on vegetation cover. Deep drainage model outputs are converted into water table variations using a lumped model add‐on. The adjustment between observed and calculated water table levels is in the order of r2 = 0.87. This correlation coefficient suggests that HYDROBAL is a useful tool to estimate groundwater recharge in the region. In addition, differences in groundwater recharge rates are observed for dry, average and wet years. Estimated recharge rates range between 0% and 18% of the mean annual rainfall, which corresponds to a net recharge of 0 to 59 mm year−1. Recharge rates increase proportionally with precipitation (r2 = 0.90). Copyright © 2012 John Wiley & Sons, Ltd.